STANDARISASI KOMPETENSI BAHASA ARAB BAGI CALON SARJANA PERGURUAN TINGGI KEAGAMAAN ISLAM NEGERI - Muhbib Abdul Wahab; Aziz Fahrurrozi; Tulus Musthafa; Syamsul Arifin (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2018)
This study aims to explore, analyze, and formulate the standard of Arabic competence for prospective graduates of S1 in UIN Jakarta and UIN Yogyakarta related to four language skills: listening, speaking, reading, and writing based on the assessment of Arabic language requirements and standards. This research used qualitative approach. In collecting the data, the researchersplayed themselve as "the main instrument" in observation, in-depth interviews, and FGD (Focussed Group Discussion). The findings of this study indicate that the competence of Arabic-based needs assessment and standard of Arabic language science is emphasized on the skills of reading and understanding Islamic texts relevant to the scholarship developed by Department and Faculty. Thus, the competence of Arabic in both UIN is accentuated on the religious orientation, namely the fulfillment of the need for understanding and scientific deepening relevant to the Prodi and the Faculty, so that Arabic is positioned as the main media in Islamic studies. These findings had implications for the importance of academic policy affirmations from UIN second leaders for the development of curricula, syllabus, teaching materials, strategies and methodologies of learning Arabic skills.